Digestibility and performance of broiler chickens fed diets with humic substances - Marcin, Andrej; Naď, Pavel; Bujňák, Lukáš; Skalická, Magdaléna (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2020)
The objective of the study was to investigate the effects of dietary intake of humic substances (HS) on the ileal digestibility of dry matter (DM) and crude protein (CP). One-day-old broiler chickens (Cobb 500, n=120, average weight 50 g) were divided at random into 4 equal groups (A, B, C / negative control). Chickens were fed with mixtures with the content of CP - BR1 230.20, BR2 222.20, BR3 209.40 g.kg-1 DM for 37 days. The applied additives HN/HNM (Humac Ltd., Slovak Republic) contained humic acids (HA) min. 650/570 and fulvic acids (FA) min. 50/50 g.kg-1. The humic substances were added into diets of experimental groups according to the content of HA/FA in the feed additives A 4.55/0.35, B 3.99/0.35, C 2.85/0.25 g.kg-1. The body weights (BW) and feed consumption were assessed once a week. The average daily weight gains (ADWG), average daily feed intake (ADFI) and the feed conversion ratio (FCR) were calculated. The ileal chymus, sampled from 48 birds after slaughter, was used for the quantification of DM, CP, ash and ash insoluble in HCl on day 37. The production parameters of chickens were from day 1 – 37 as follows. The average finishing body weights were A 2506.67 ± 160.47, B 2490.25 ± 166.39, C 2377.75 ± 133.19 and control 2319.42 ± 92.55 g. The average weight gains achieved the values A 66.39 ± 16.85, B 65.95 ± 17.77, C 62.91 ± 18.06 and control 61.34 ± 17.31 g.day-1. The average daily feed intakes were A 108.97 ± 50.11, B 116.91 ± 55.35, C 108.85 ± 51.44 and control 106.83 ± 46.97 g.day-1 from day 1 – 37. The addition of humic substances caused the increase of ileal digestibility in B group compared to control: DM 38.32 ± 0.18 / 30.94 ± 2.41% (p < 0.05) and CP 40.39 ± 0.05 / 34.29 ± 0.26% (p < 0.05). The dietary intake of feed additives containing HS seems to have a positive effect on finishing BW and the ileal digestibility of DM and CP in the case of the minimal inclusion level of HA/FA 3.99/0.35 g.kg-1.